PENGARUH RELIGIUSITAS TERHADAP RESILIENSI PADA SANTRI PONDOK PESANTREN - Suprapto, Savira Annisa Putri (Cognicia, 2020)
The role of religiosity is needed to developing resilience behavior in students in Islamic boarding schools so that students can overcome existing problems despite being under pressure. One of the factors that can influence resilience is religiosity, religiosity is needed in a student as a solution if a problem occurs even though the student is in a depressed state because of the many activities carried out in Islamic boarding schools. The purpose of this research is to find out how much influence the religiosity variable has on resilience. In this study, researchers used quantitative research with a sampling technique that is stratified random sampling. In this study, researchers used boarding school students as its subjects. With a range of grades 7,8,9 in junior high school level and 10,11,12 in 221 levels of respondents in Batu City. The instruments in this study used the Seven dimension of Religiosity scale from Kendler (2003) and Connor Davidson Resilience Scale (CD-RISC 25). Analysis of the data used in this study is a simple linear regression test. The results of this study indicate that there is a significant influence between the variables of religiosity on resilience variables. (R2 = 0.741; p = 0,000)